Effect of vibro-milling on dielectric properties of barium zirconium titanate ceramics - Chatchai Kruea-In (2018)
Barium zirconium titanate powders were prepared by conventional ball milling and vibro-milling methods. Barium zirconium titanate ceramics were fabricated from the obtained powders. Properties of the ceramics were investigated. The vibro-milling ceramics showed a better dielectric constant and relative tunability. It is proposed that the better densification and degree of crystallinity for the vibro-milling ceramics are responsible for better ceramics properties. Copyright © Taylor &Francis Group, LLC.